Efficacy of Chewing Gum and Acupressure in Digestive Function Post-Abdominal Surgery: A Systematic Review - Pratama, Yudha; Sriyono, Sriyono; Qona’ah, Arina (GLOBAL HEALTH SCIENCE GROUP, 2024)
Recovery of digestive function after abdominal surgery is often a challenge for patients, mainly due to nutritional disturbances caused by pain and inability to eat. This can slow down the healing process and prolong recovery time. Pain in the surgical area also inhibits patient movement, which worsens gastrointestinal motility. Complications such as difficulty in flatus and defecation can result in abdominal distension and increase length of hospitalization. This study aims to explore the effectiveness of non-pharmacological interventions, namely chewing gum and acupressure, in accelerating the recovery of gastrointestinal function in patients after abdominal surgery. Methods: The search strategy involved a systematic review using four electronic databases: Pubmed, Science Direct, Proquest, Taylor and Francis, and Scopus. The search was conducted on February 20, 2024, and focused on articles published from 2019 to 2024 in English. The search terms “Chewing Gum” AND “Acupuncture” OR “Acupuncture Points” OR “ST 36 Point” AND “Non-pharmacological Therapy” AND “Postoperative Period” AND “Abdominal Surgery” AND “Digestive” AND “System” AND “Function” AND “Recovery”. After removing duplicates and filtering based on title, abstract, and eligibility, 18 articles were selected for the review using PRISMA. Result: The study found 1.098 articles and reviewed 18 articles the study reviewed the effectiveness of non-pharmacological interventions, specifically chewing gum and acupressure, in enhancing digestive recovery following abdominal surgery. Results indicated that both methods significantly improved gastrointestinal function, evidenced by faster bowel motility and reduced hospital stays. The findings suggest that implementing these interventions could provide effective support in postoperative care, addressing common complications such as delayed bowel movement and abdominal distension.Conclusion: The combination of chewing gum and acupressure can significantly accelerate the recovery of digestive function in post-abdominal surgery patients, making it an effective non-pharmacological method to improve post-surgical care.